Financial Ratio Analysis PT Indofood Sukses Makmur, Tbk - Dahlan Palenteng (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to analyze the financial ratios of PT Indofood Sukses Makmur Tbk during the period 2015 to 2021 to see the company's performance. This study uses secondary data in the form of financial reports. The analytical tool used in this study is to use liquidity ratios, solvency ratios, activity ratios, profitability ratios, and market price ratios. The results of the calculation of the liquidity ratio which consists of the quick ratio and cash ratio are considered not good, while the current ratio is considered quite good. The solvency ratio consisting of the debt to asset ratio is considered quite good, and the debt to equity ratio is considered not good. The activity ratio, which consists of total asset turnover ratio and fixed asset turnover ratio, is considered unfavorable. For the profitability ratio which consists of the ratio of return on assets, and the ratio of return on equity, and the ratio of net income is considered not good. And the market to book ratio is considered quite good.